Plan de negocios a través del modelo my.coop para la asociación Quimquinagro del municipio de Quimbaya departamento del Quindío, vinculada a la Fundación Fundecompe (2016)
This work is the result of the internship made at the Fundación para el desarrollo y la competitividad (Fundecompe), which was aimed at the strengthening of the Quimquinagro association of the municipality of Quimbaya, for this, initially an entrepreneurial diagnosis was made on which evaluated eight aspects so that could identify their strengths and weaknesses, giving way to the development of a business plan, which would allow to the association apply for grants in the various government agencies in order to carry out projects that contribute to growth and strengthening of the association, as also access to the public call of the Ministry of Agriculture in order to get resources that favored sustainability of the association, and finally, the socialization of the business plan with its members was made.